2014
DOI: 10.1038/npp.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid Type 1 Channel May Modulate Opioid Reward

Abstract: Transient receptor potential vanilloid type 1 (TRPV1), a nonselective cation channel, is a well-known pain-related receptor. TRPV1 involvement in morphine-induced antinociception, tolerance, and withdrawal symptoms has been previously reported. Emerging evidence indicates that TRPV1 may be related to both the cellular and behavioral effects of addictive drugs. In the present study, we investigated the role of TRPV1 in morphine reward using the conditioned place preference (CPP) paradigm in mice. Repeated morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…It seems that other than in dorsal striatum, TRPV1 participates in morphine reward also in the cortex, nucleus accumbens, and ventral tegmental area (338). Further experimental data suggest that TRPV1 contributes to morphine reward via adenylyl cyclase 1, p38 MAPK, and NF-B (624). In a rat model of cocaine addiction, a TRPV1 receptor antagonist decreases cocaine-seeking behavior in the reinstatement phase, although TRPV1 seems to be unnecessary for the rewarding effect of cocaine (3).…”
Section: Rewardmentioning
confidence: 96%
“…It seems that other than in dorsal striatum, TRPV1 participates in morphine reward also in the cortex, nucleus accumbens, and ventral tegmental area (338). Further experimental data suggest that TRPV1 contributes to morphine reward via adenylyl cyclase 1, p38 MAPK, and NF-B (624). In a rat model of cocaine addiction, a TRPV1 receptor antagonist decreases cocaine-seeking behavior in the reinstatement phase, although TRPV1 seems to be unnecessary for the rewarding effect of cocaine (3).…”
Section: Rewardmentioning
confidence: 96%
“…In addition to these activators, TRPV1 levels in DRG neurons were increased by nerve growth factor and the activation of p38 mitogen-activated protein kinase in inflamed skin [ 38 ]. It has also been suggested that the TRPV1 channel is activated by phosphatidylinositol 3-kinase-induced heat hyperalgesia [ 39 , 40 ]. In addition, the TRPV1 channel is activated by low pH [ 41 , 42 ].…”
Section: Trp Channelsmentioning
confidence: 99%
“…Previous evidence showed that positive modulation of the TRPV1 channels could be a potential target for mitigation of AD (Jayant et al, 2016), suggesting an important involvement of TRPV1 in AD. In addition, Nguyen et al (2014) have also shown that TRPV1 plays a key role in morphine addiction. Blednov and Harris (2009) showed that the deletion of TRPV1 in mice altered behavioral effects of ethanol which indicates a connection between TRPV1 and alcoholism.…”
Section: Application Of Cmm To Two Gwas Data Sets For Ad and Sudsmentioning
confidence: 98%